Accuracy of interleukin-27 assay for the diagnosis of tuberculous pleurisy: A PRISMA-compliant meta-analysis. Issue 50 (December 2017) - Li, Min; Zhu, Wenye; Khan, Rana Sami Ullah; Saeed, Ummair; Wang, Rongchun; Shi, Shaoqing; Luo, Zhuang
Abstract: Background: The concentration of interleukin-27 (IL-27) in pleural effusions was found to be increased in tuberculous pleurisy and several studies have investigated the diagnostic value of IL-27 for tuberculous pleural effusions (TPEs), but the results varied a lot. We conducted the present study to comprehensively evaluate the diagnostic value of IL-27 for TPE. Methods: Primary diagnostic test studies of IL-27 for TPE was searched and identified from databases. The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ration, diagnostic odds ratio, and receiver operating characteristic curves (SROCs) were computed or pooled to summarize the overall test performance. Results: Nine studies with a total number of 1226 patients were identified in our research. The main pooled estimates were as follows: sensitivity 0.92 [95% confidence interval (CI), 0.90–0.95], specificity 0.90 (95% CI, 088–0.92), and area under the SROC 0.97. No evidence of publication bias was detected. Conclusion: Our research suggested the good diagnostic value of IL-27 for TPE and it could be used as a diagnostic biomarker.